Digitalization of investment processes: risk- management and economic security (Economics and region, 2023)
The article discusses the risks and economic security associated with the digitalization of investment processes, including the use of blockchain technologies, smart contracts and robot advisors. The process of digitalization in the investment sphere is analyzed, the main risks are identified. Analysis of the causes and consequences of the widespread use of digital technologies in the field of investment led to the conclusion that digital technologies have gained great popularity in the investment sphere. The paper identifies strategies for ensuring economic security in the context of digital investments, as well as regulatory aspects and regulatory requirements. A study of trends related to digitalization of investment processes has been carried out, which has revealed changes in the process of making managerial decisions on investment and provides general trends in changes in directions and spheres of investments.
Keywords: digitalization; investment processes; risk; economic security; digital technologies